Work and the welfare state : street-level organizations and workfare politics - Brodkin, Evelyn Z.; Marston, Gregory (Public management and change., 2013)
This book places street-level organizations at the analytic center of welfare-state politics, policy, and management. This volume offers a critical examination of efforts to change the welfare state to a workfare state by looking at on-the-ground issues in six countries: the US, UK, Australia, Denmark, Germany, and the Netherlands. An international group of scholars contribute organizational studies that shed light on old debates about policies of workfare and activation. Peeling back the political rhetoric and technical policy jargon, these studies investigate what really goes on in the name of workfare and activation policies and what that means for the poor, unemployed, and marginalized populations subject to these policies. By adopting a street-level approach to welfare state research, this book reveals the critical, yet largely hidden, role of governance and management reforms in the evolution of the global workfare project. It shows how these reforms have altered organizational arrangements and practices to emphasize workfare's harsher regulatory features and undermine its potentially enabling ones. As a contribution to expanding the conceptualization of how organizations matter to policy and political transformation, this book will be of interest to public management and public policy scholars and students. -- Publisher's description.